Chromatographic analysis of aflatoxigenic Aspergillus flavus isolated from Malaysian sweet corn - Khan, Rahim; Mohamad Ghazali, Farinazleen; Mahyudin, Nor Ainy; Samsudin, Nik Iskandar Putra (Multidisciplinary Digital Publishing Institute, 2021)
High-performance liquid chromatography (HPLC) provides a quick and efficient tool for accurately characterizing aflatoxigenic and non-aflatoxigenic isolates of Aspergillus flavus. This method also provides a quantitative analysis of AFs in Aspergillus flavus. The method’s recovery was assessed by spiking a mixture of AF at different concentrations to the testing medium. The validity of the method was confirmed using aflatoxigenic and non-aflatoxigenic strains of A. flavus. The HPLC system, coupled with a fluorescence detector and post-column photochemical reactor, showed high sensitivity in detecting spiked AFs or AFs produced by A. flavus isolates. Recovery from medium spiked with 10, 20, 60, and 80 ppb of AFs was found to be 73–86% using this approach. For AFB1 and AFB2, the limit of detection was 0.072 and 0.062 ppb, while the limit of quantification was 0.220 and 0.189 ppb, respectively. The AFB1 concentrations ranged from 0.09 to 50.68 ppb, while the AFB2 concentrations ranged between 0.33 and 9.23 ppb. The findings showed that six isolates produced more AFB1 and AFB2 than the acceptable limit of 5 ppb. The incidence of aflatoxigenic isolates of A. flavus in sweet corn and higher concentrations of AFB1 and AFB2 emphasize the need for field trials to explore their real potential for AF production in corn.